El derecho a la defensa en los procesos de impugnación de las contravenciones de tránsito, en la ciudad de Machala, en el año 2014. Propuesta de reforma a los artículos: 383 al 392 del código orgánico integral penal. - Marín Gonzabay, Edwin Josmer (2015)
The research aims to clear certain variables regarding the question asked: "THE RIGHT TO DEFENSE IN THE PROCESS OF CHALLENGING THE TRAFFIC VIOLATIONS IN the city of Machala, in 2014. PROPOSAL TO REFORM ARTICLES 383 TO 392 OF THE PENAL CODE ORGANIC INTEGRAL ". A thorough analysis of the legal effects wills also a comparative study of the different legislation, which is why we've broken down the investigative work into the following chapters.